Surface Functionalized Cellulose Nanocrystals for Synthetic Latex Property Modification - Kedzior, Stephanie (My University, 2017)
The objective of this thesis is to incorporate cellulose nanocrystals (CNCs) into polymer latexes prepared using various emulsion polymerization methods. CNCs are a promising new class of renewable materials with unique properties including nanoscale dimensions, a high aspect ratio, low density, and high strength. They show significant promise to enhance the properties of existing materials, but challenges often arise due to incompatibility and processing difficulties. This work investigates novel surface modification routes to improve the compatibility of CNCs with emulsion polymerization components, and aims to control the location and function of CNCs in latex systems in order to modify latex properties. Three approaches to incorporate CNCs into polymer latexes are presented: (1) exploiting CNC-surfactant interactions in order to promote CNCs as Pickering stabilizers or as “passive” additives in the water phase, (2) enhancing the surface activity of CNCs by adsorbing the surface active biopolymer methyl cellulose (MC) to act as Pickering co-stabilizers, or (3) hydrophobic modification of CNCs through polymer grafting in order to provide improved compatibility between CNCs and the monomer/polymer phase to incorporate CNCs into the latex core. First, the interactions between CNCs and surfactants were studied in suspension and at surfaces and the CNC-surfactant combinations were used to stabilize miniemulsion polymerization of methyl methacrylate (MMA), a model system used in this work. Oppositely charged CNCs and surfactants showed improved stability as Pickering stabilizers and the ability to co-stabilize the monomer/polymer-water interface. When like-charged CNCs and surfactants were used, the poly(methyl methacrylate) (PMMA) polymer particles were stabilized by surfactant only, while the CNCs remained in the water phase. Next, in order to avoid the use of surfactants, CNCs were coated with MC to provide improved surface activity. MC-coated CNCs were effectively used as Pickering stabilizers in the microsuspension polymerization of MMA, where a double morphology of PMMA particles was observed, and the morphology could be tuned based on the ratio of CNC to MC used. Finally, CNCs were modified with hydrophobic polymer via two different “grafting from” methods: free radical polymerization and atom transfer radical polymerization (ATRP). Free radical polymer grafting from CNCs resulted in polymer-grafted CNCs but the method lacked control over polymer graft length and graft density. To overcome this, CNCs were modified via surface initiated ATRP where considerably higher amounts of polymer were grafted from the CNCs in short reaction times and with simple purification steps. Furthermore, polymer-grafted CNCs were added to the monomer phase of the miniemulsion polymerization of MMA and latexes with CNCs inside the hydrophobic polymer particle core were prepared. Given the difficulties in characterizing polymer grafted CNCs, a novel solution state NMR method was used, whereby the modified CNCs were dissolved in ionic liquids and the polymer grafts were cleaved and collected to determine graft length and graft density. Overall, this work provides three approaches for the preparation of nanocomposite latexes with CNCs using PMMA as a model system. The results presented here may expand the use of CNCs in latex products such as adhesives, paints, coatings, and cosmetics.
Keywords: cellulose nanocrystals; synthetic latex; polymer chemistry; polymer grafting